The relationship between family affective functions and bullying behavior in school-age children in Malang City, Indonesia - Roemahlaiselan, Sindy Olivia; Windarwati, Heni Dwi; Hidayah, Ridhoyanti; Nova, Renny (PT Saintek Medika Nusantara, 2021)
Bullying is a global phenomenon that occurs all over the world. One of the factors thought to be closely related to bullying is the affective function of the family. This study aims to analyze the relationship between family affective function and bullying behavior in school-age children in Malang, Indonesia. This study used a cross-sectional approach. The measuring instrument used is the bullying behavior questionnaire (Sejiwa) and the family affective function questionnaire (Family Assessment Device/FAD). The sample of this study was 44 students aged 10-12 years. The results show that the family's affective function is in the moderate category, and bullying behavior is in the low category. Bivariate analysis showed the relationship between family affective function and bullying behavior in school-age children using the Spearman Rank test, p=0.002. This study shows that the affective functions of the family are closely related to bullying behavior in school children. This research can be used to provide group counseling therapy regarding affective functions in the family to reduce the incidence of bullying behavior. This therapy can be applied by psychiatric nursing practitioners both in the school community and to families during interventions, through counseling about the affective function of the family. This research may provide a solution for handling bullying behavior in school children.